2014
DOI: 10.1016/j.jprot.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

O-linked glycosylation sites profiling in Mycobacterium tuberculosis culture filtrate proteins

Abstract: Mycobacterium tuberculosis (Mtb) causes tuberculosis, one of the leading causes of fatal infectious diseases worldwide. Cell-cell recognition between the pathogen Mtb and its host are mediated in part by glycosylated proteins. So far, glycoproteins in Mtb are understudied and for only very few glycoproteins glycosylation sites have been described, e.g., alanine and proline rich secreted protein apa, superoxide dismutase SODC, lipoprotein lpqH and MPB83/MPT83. In this study, glycosylated proteins in Mtb culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 24 publications
9
49
0
Order By: Relevance
“…Acetylation [60] and phosphorylation [6165] are the most common modifications in Mtb. Moreover, O-glycosylation [66,67], Pupylation (Prokaryotic Ubiquitin-Like Protein Modification) [68], lipidation [66], methylation, deamidation and N-formylation have been reported (Fig 2b, 2c) [69]. Our analysis also showed that specific types of modifications can be enriched in specific functional categories.…”
Section: Current Knowledge About the Proteome Of Mtbsupporting
confidence: 55%
“…Acetylation [60] and phosphorylation [6165] are the most common modifications in Mtb. Moreover, O-glycosylation [66,67], Pupylation (Prokaryotic Ubiquitin-Like Protein Modification) [68], lipidation [66], methylation, deamidation and N-formylation have been reported (Fig 2b, 2c) [69]. Our analysis also showed that specific types of modifications can be enriched in specific functional categories.…”
Section: Current Knowledge About the Proteome Of Mtbsupporting
confidence: 55%
“…MS-based proteomics has also been applied to identify specific O-mannosylation sites, for instance, on an isolated culture filtrate protein (FasC) of M. smegmatis in a study on bacterial protein-O-mannosylating enzyme (92). Furthermore, glycosylation sites for an additional 13 M. tuberculosis culture filtrate proteins were recently reported (93). (94,95).…”
Section: Glycosylationmentioning
confidence: 99%
“…Several proteins of Mtb complex species have been identified as glycoproteins on the basis of lectin binding (Espitia et al ., 1989; Garbe et al ., 1993; Gonzalez-Zamorano et al, 2009; Sartain and Belisle, 2009) or by using liquid chromatography-mass spectrometry approaches and bioinformatic analyses (Smith et al ., 2013), but the detailed structure of the glycosyl appendages of only two of them have been characterized so far. The 45-47 kDa (Apa) antigen of Mtb was shown to be modified at threonine residues with one to three linear α–(1,2)-linked oligomannosides, whereas the MBP83 antigen of M. bovis is modified at threonine residues with one to three linear α–(1,3)-linked oligomannosides (Dobos et al ., 1996; Michell et al ., 2003).…”
Section: The Major Cell Envelope Glycoconjugates Of Mtbmentioning
confidence: 99%